Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas V Di UPT SDN 064985 Medan Helvetia - Erika Kristina Pasaribu; Muhammad Arif (Kilau Publishing, 2024)
The problem in this research is the number of students who get grades below the KKM in science lessons at UPT SD Negeri 064985 Medan Helvetia. The low student learning outcomes are due to the delivery of learning material still using the lecture method and not using interesting learning media. This research aims to improve student learning outcomes in science learning in class V by applying the Problem Based Learning (PBL) model. Through this PBL model, students are given the opportunity to solve problems independently. This research includes classroom action research (PTK) which was carried out in 2 cycles. The instruments of this research are tests made by the teacher, observation sheets consisting of teacher activities and student activities, group assignments and documentation. The findings of this research are that the application of the problem based learning model can improve the activities and learning outcomes of fifth grade students in science subjects. It can be seen that in cycle I the average class score reached 71.3 and students who achieved the KKM was 67.86%. In cycle II the average class score reached 86.48 and students who achieved the KKM was 89.29%. Thus it can be concluded that the application of the problem based learning model is effective in improving student learning outcomes in science subjects for class V students at UPT SD Negeri 064985 Medan Helvetia.